Geoform: dispositivos aplicados às ações de saúde pública no município de Benevides, PA - PEREIRA, Gabriel Miranda (2023)
This work aims to propose a tool to subsidize the public health system in the construction and organization of databases through geolocation techniques, using the GEOFORM application as an instrument, aiming to facilitate care in health services and streamline the storage and access to patient information. To reach the objectives, the research was based on a bibliographic review, application of 20 questionnaires with families living in the city of Benevides and development of software using .NET, C#, Java. It is expected to subsidize the activities of health agents in recording data by filling out forms including geolocation data, aiming to contribute to the application of efficient strategies for public health policy actions in a local context.